Hubungan Antara Nilai Neutrophil-to-Lymphocyte Ratio (NLR) dengan Kadar Procalcitonin (PCT) pada Pasien COVID-19 di Kabupaten Jember - Rafida, Sofia Yusnur; Hairrudin, Hairrudin; Hasan, Muhammad (Faculty of Medicine, Universitas Andalas, 2022)
The neutrophil-to-lymphocyte ratio (NLR) and Procalcitonin (PCT) are biomarkers that represent inflammatory activity and immune status as predictors for the prognosis of COVID-19 patients. NLR values and PCT levels are positively correlated with the severity of COVID-19, but the relationship between the two biomarkers is unclear. Objectives: To analyzed the correlation between NLR values and PCT levels in COVID-19 patients in Jember Regency. Methods: This cross-sectional analytic observational study, conducted from March to April 2022, took data from 444 confirmed COVID-19 patients at the Jember Clinic Plantation Hospital. Secondary data were obtained from medical records of inpatients for the period Januaryâ€“December 2021. Results: The average NLR value was 8.58, while the average PCT level was 0.43 ng/mL. The results of the Spearman Correlation Analysis showed a positive correlation between NLR values and PCT levels in COVID-19 patients in the Jember Regency with a p-value = 0.00 and a moderate degree of correlation with an r count of 0.41. Conclusion: There is a positive correlation between NLR values and PCT levels for COVID-19 patients in Jember Regency. It is necessary to carry out routine NLR and PCT examinations to consider predictors of disease severity and prognosis in COVID-19 patients.Keywords: Â COVID-19, NLR, PCT